Fatty acids in multiple circulating lipid fractions reflects the composition of liver triglycerides in humans. Issue 4 (April 2022) - Rosqvist, Fredrik; Fridén, Michael; Vessby, Johan; Hockings, Paul; Hulthe, Johannes; Gummesson, Anders; Niessen, Heiko G.; Schultheis, Christian; Wanders, Alkwin; Ahlström, Håkan; Rorsman, Fredrik; Risérus, Ulf
Summary: Background and aims: Fatty acids (e.g. 16:1n-7) and desaturase indices (e.g. stearoyl-CoA desaturase, SCD) in plasma cholesteryl esters (CE) and phospholipids (PL) are used as biomarkers of dietary fat quality and lipid metabolism and are associated with disease outcomes. Endogenously produced circulating fatty acids are believed to reflect composition of the liver, yet little data exist to support such relationship. We investigated associations between circulating fatty acids and fatty acids within the liver. Methods: Liver biopsies and blood were collected from n = 60 patients with non-alcoholic fatty liver disease. Fatty acids in CE, PL and triglycerides (TG) in plasma and liver were analyzed using gas chromatography. Associations were assessed using Spearman rank correlations. Results: Overall, fatty acids and desaturase indices in plasma PL and TG showed moderate–strong correlations with fatty acids and desaturase indices in corresponding lipid fractions in liver. For plasma CE, 16:1n-7 and SCD were correlated with 16:1n-7 and SCD in liver CE. Noteworthy, fatty acids in plasma CE and PL also showed moderate–strong correlations with fatty acids in liver TG (e.g. r = 0.82–0.87 for 16:1n-7 and r = 0.77 for SCD). Conclusion: We demonstrate that fatty acids in circulating lipid fractions, including CE, TG and PL, reflects the composition of liver TG in humans, suggesting that circulating fatty acids might be useful biomarkers for the fatty acid composition of the liver. As liver tissue is rarely available in cohort studies, our findings could enhance our understanding of plasma fatty acids as markers of hepatic lipid metabolism and their links to metabolic diseases.